Augmented reality and mixed reality for healthcare education beyond surgery: an integrative review - Gerup, Jaris (Int J Med Educ, 2020)
OBJECTIVES: This study aimed to review and synthesize the current research and state of augmented reality (AR), mixed reality (MR) and the applications developed for healthcare education beyond surgery. METHODS: An integrative review was conducted on all relevant material, drawing on different data sources, including the databases of PubMed, PsycINFO, and ERIC from January 2013 till September 2018. Inductive content analysis and qualitative synthesis were performed. Additionally, the quality of the studies was assessed with different structured tools. RESULTS: Twenty-six studies were included. Studies based on both AR and MR involved established applications in 27% of all cases (n=6), the rest being prototypes. The most frequently studied subjects were related to anatomy and anesthesia (n=13). All studies showed several healthcare educational benefits of AR and MR, significantly outperforming traditional learning approaches in 11 studies examining various outcomes. Studies had a low-to-medium quality overall with a MERSQI mean of 12.26 (SD=2.63), while the single qualitative study had high quality. CONCLUSIONS: This review suggests the progress of learning approaches based on AR and MR for various medical subjects while moving the research base away from feasibility studies on prototypes. Yet, lacking validity of study conclusions, heterogeneity of research designs and widely varied reporting challenges transferability of the findings in the studies included in the review. Future studies should examine suitable research designs and instructional objectives achievable by AR and MR-based applications to strengthen the evidence base, making it relevant for medical educators and institutions to apply the technologies.